The Impact of Omnichannel Properties on Customer Engagement and Loyalty in Banking: An SOR Perspective - Andika; Nasution, Atika Aini; Luthfiana, Della Nanda; Ihsan, Akmal; Yuanidhar, Fazah (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study will thoroughly explore the effects of the quality of integration, perceived fluidity, and the reliability of assurances on cognitive and emotional engagement and customer loyalty within the banking sector. The investigation will be conducted in an omnichannel context using the stimulus-organism-response (SOR) framework. Design/Methods/Approach: This research utilized an online survey distributed via personal messages to collect data from bank customers who actively use omnichannel banking services. Employing a non-probabilistic purposive sampling technique, the study ensured respondents met specific criteria, resulting in 275 valid responses, which were analyzed using Smart PLS-SEM 4.0 to verify the proposed hypotheses. Findings: This study found that the quality of integration and perceived fluidity significantly affect cognitive and emotional customer engagement. Interestingly, the reliability of assurances impacts only cognitive engagement rather than emotional engagement. These two forms of engagement, cognitive and emotional, substantially enhance brand loyalty in the omnichannel banking context. Originality/Value: This study contributes significantly to the existing literature by providing a holistic perspective on customer engagement in the banking sector during the omnichannel era. Unlike previous studies, this research integrates three key dimensions within omnichannel banking: the quality of integration, perceived fluidity, and the reliability of assurances. Using the SOR framework, it explores their impact on cognitive and emotional engagement and customer loyalty. The findings not only deepen the understanding of effective service channel management to enhance customer engagement and loyalty but also offer practical guidance for the banking industry in designing more effective omnichannel strategies. Practical/Policy implications: This study's findings provide valuable insights for banks in the omnichannel banking sector. The research indicates that banks must optimize integration quality across service channels to enhance customer engagement and loyalty. Banks should adopt technologies that enable real-time data synchronization and train staff to ensure service consistency across all channels. Additionally, banks should develop effective loyalty programs to maintain cognitive and emotional customer engagement and actively collect feedback to improve customer experience continuously.